Healthy Eating: Folate - Linda B. Bobroff (EDIS, 2012)
Folate is one of the B vitamins. Our bodies use folate to make new cells. Folate is especially important for women of childbearing age, pregnant and nursing women, growing children, and older people. If you don’t get enough folate in your diet, you could get anemia. You also could be at higher risk for heart disease, stroke, cancer, or memory problems. This revised 1-page large print fact sheet was written by Linda B. Bobroff and published by the UF Department of Family, Youth and Community Sciences, September 2012.